Guidelines for Neuroleptic Relapse Prevention in Schizophrenia Proceedings of a Consensus Conference held April 19–20, 1989, in Bruges, Belgium - Kissling, Werner (Springer Berlin Heidelberg, 1991)
How neuroleptics are used in relapse prevention is a very controversial topic. Fifty percent of all schizo- phrenic patients do not receive sufficient prophylactic treatment and suffer from frequent relapses. To help correct this situation, leading international experts in the field of neuroleptic relapse prevention (n.r.p.) agreed upon guidelines after intensive discussions at a consensus workshop in Bruges in April 1989. Precise guidelines to the most important questions on n.r.p. are formu- lated, especially concerning indications, treatment duration and dosage. The current state of the literature on these questions is presented in comprehensive reviews. For the practicing psychiatrist or general practitioner, exact guidelines for prophylactic treatment are presented; for patients and their families eager to obtain more information, the scientific basis of the treatment is explained
Keywords: Psychiatry; Neuroleptikum; Internationaler Vergleich; Rezidivprophylaxe; Schizophrenie; Konferenzschrift -- 1989 -- Brügge